The potential for adaptation in the model plant, Arabidopsis, and its close relative, Boechera - Lovell, John Thomson, author; McKay, John K., advisor; Ghalambor, Cameron K., committee member; Bauerle, William L., committee member; Angert, Amy L., committee member (Colorado State University. Libraries, 2014)
Populations of a species are found across diverse environments. Frequently, evolutionary responses to varying natural selection pressures across environments cause adaptive differentiation among populations. For plants with limited dispersal capability, adaptation is the primary way populations can persist through changing environments and climates. Therefore, factors that constrain adaptation can directly affect the conservation status and future distributions of species and populations. Contemporary adaptations, via either selection on standing genetic variation or new beneficial mutations that sweep to fixation, have been observed across many taxonomic groups. However, these events of fast, streamlined adaptive evolution may be rare. Instead, adaptation is often constrained by both ecological and genetic forces. Determining the mechanisms and ecological manifestations of adaptive constraint remains a major challenge for evolutionary biologists, conservation biologists and crop breeders. The primary goal of my dissertation research is to address this challenge. The research projects described herein documented the extent and causes of evolutionary constraint by accomplishing three separate goals: (1) to document genes underlying drought adaptation in the model plant, Arabidopsis thaliana, to infer the adaptive effects of pleiotropy, (2) to determine the mechanisms constraining adaptation in rare species relative to widespread congeners, and (3) to assess the degree of adaptive differentiation across the genomic loci and populations. By measuring quantitative and molecular diversity across several species, I determined the relative potential of adaptation at the gene, population, and species levels of organization. In chapter 2 I studied adaptation at the gene-level and demonstrated that the Arabidopsis thaliana gene FRI (FRIGIDA) exhibits adaptive pleiotropy. Through simultaneous genetic effects on many traits, variation at the single gene FRI produces trait correlations along an axis that is in line with the vector of selection. In this case, sequence polymorphism at FRI caused phenotypic co-variance of water-use-efficiency (WUE), relative growth rate and timing of flowering. This genetic correlation coincided with a well-described adaptive correlation found in natural and agricultural systems. In chapter 3, I studied the processes that cause range size diversity across species, by comparing population ecology and genetics of species with broadly divergent range sizes. I assayed the heritability of potentially adaptive traits and other quantitative genetic statistics from multiple rare and widespread species and found that rare species lack heritable genetic variation and physiological plasticity. Combined, these factors place rare species at increased risk of extinction across changing environmental conditions. In chapter 4, I studied adaptation at the population level. I examined how environmental variation impacted genomic structure, selection pressures and local adaptation in Boechera spatifolia (Brassicaceae), a species that contains both sexual and asexual (apomictic) individuals. I found that, despite occupying sympatric sites, apomictic lineages are both phenotypically and genetically distinct from sexuals. Additionally, while sexual populations formed strong clines (both genomic and physiological) along latitude and elevation gradients, apomicts showed no such signature of local adaptation.
Keywords: Boechera; drought; adaptation; Arabidopsis; Apomixis